Pengaruh Scramble Berbasis IT Dalam Meningkatkan Pemahaman Tarakib Nahwiyyah - Dodi Robiansyah; Rohid Vatullah; Ii Rahmanudin; Burhan Lukman Syah (Justek : Jurnal Sains dan Teknologi, 2022)
Abstract: Scramble learning model is a learning model that provides an interesting and fun learning atmosphere. In addition, this learning model can improve student responsiveness during learning because it is required to actively develop creativity and think to solve tarakib problems using this model. Scrambel has often been used in general lessons but not in Arabic lessons. So that the purpose of this study can be taken to find out Arabic learning in tarakib understanding of the material "Religion in Indonesia" before and after the use of IT-based Scramble and to determine the effect of using IT-based Scramble on Arabic learning outcomes in tarakib understanding of the material "Religion in Indonesia” for 11th grade students at Madrasah Aliyah Negeri 4 Cirebon. The method in this study uses quantitative methods. Pre-experimental in the form of one group pretest posttest design and data collection in this study using interviews, observations and tests and the technique is simple random sampling to measure student learning outcomes in tarakbi understanding of the material "Religion in Indonesia". The results of the pretest on the understanding of tarakib nahwiyyah of grade 11 students at Madrasah Aliyah Negeri 4 Cirebon before using the Scramble with an average of 56.3 and student learning outcomes after using the Scramble seen from the posttest test with an average of 76.7. The effect of using Scramble on Arabic learning outcomes on the understanding of tarakib nahwiyyah 11th graders at Madrasah Aliyah Negeri 4 Cirebon shows a significant influence and the evidence is that the results of the study were calculated using a paired simple t-test with the results of sig (2-tailed) 0.000 < 0.005 and the result of Cohen's effect size calculation is 5.55 with a sample of 31 students. It means that the Scramble learning model has a strong and high impact. Then Ha is accepted, HO is rejected.Abstract: Scramble learning model is a learning model that provides an interesting and fun learning atmosphere. In addition, this learning model can improve student responsiveness during learning because it is required to actively develop creativity and think to solve tarakib problems using this model. Scrambel has often been used in general lessons but not in Arabic lessons. So that the purpose of this study can be taken to find out Arabic learning in tarakib understanding of the material "Religion in Indonesia" before and after the use of IT-based Scramble and to determine the effect of using IT-based Scramble on Arabic learning outcomes in tarakib understanding of the material "Religion in Indonesia” for 11th grade students at Madrasah Aliyah Negeri 4 Cirebon. The method in this study uses quantitative methods. Pre-experimental in the form of one group pretest posttest design and data collection in this study using interviews, observations and tests and the technique is simple random sampling to measure student learning outcomes in tarakbi understanding of the material "Religion in Indonesia". The results of the pretest on the understanding of tarakib nahwiyyah of grade 11 students at Madrasah Aliyah Negeri 4 Cirebon before using the Scramble with an average of 56.3 and student learning outcomes after using the Scramble seen from the posttest test with an average of 76.7. The effect of using Scramble on Arabic learning outcomes on the understanding of tarakib nahwiyyah 11th graders at Madrasah Aliyah Negeri 4 Cirebon shows a significant influence and the evidence is that the results of the study were calculated using a paired simple t-test with the results of sig (2-tailed) 0.000 < 0.005 and the result of Cohen's effect size calculation is 5.55 with a sample of 31 students. It means that the Scramble learning model has a strong and high impact. Then Ha is accepted, HO is rejected.Abstrak: Model pembelajaran Scramble merupakan model pembelajaran yang memberikan suasana belajar yang menarik dan menyenangkan. Selain itu, model pembelajaran ini dapat meningkatkan daya tanggap siswa saat pembelajaran karena dituntut aktif mengembangkan kreatifitas dan berpikir untuk memecahkan masalah tarakib dengan menggunakan model ini. Scrambel sudah sering digunakan dalam pembelajaran pelajaran umum tapi belum pada pelajaran bahasa Arab. Sehingga dapat diambil tujuan dari penelitian ini untuk mengetahui pembelajaran Bahasa arab dalam pemahaman tarakib tentang materi “Agama di Indonesia” sebelum dan sesudah penggunaan Scramble berbasis IT dan untuk mengetahui pengaruh penggunaan Scramble berbasis IT terhadap hasil belajar Bahasa arab dalam pemahaman tarakib tentang materi “Agama di Indonesia” untuk siswa kelas 11 di Madrasah Aliyah Negeri 4 Cirebon. Metode dalam penelitian ini menggunakan metode kuantitatif. Secara Pre eksperimental dengan bentuk rancangan one group pretest posttest dan Pengumpulan data dalam penelitian ini menggunakan wawancara, observasi dan tes dan tekniknya simple random sampling untuk mengukur hasil belajar siswa pada pemahaman tarakbi tentang materi “Agama di Indonesia”. Hasil pretest pada pemahaman tarakib nahwiyyah  siswa kelas 11 di Madrasah Aliyah Negeri 4 Cirebon sebelum menggunakan Scramble yaitu dengan rata-rata 56,3 dan hasil belajar siswa setelah menggunakan Scramble dilihat dari tes posttest yaitu dengan rata-rata 76,7. Adapun pengaruh penggunaan Scramble terhadap hasil belajar Bahasa arab pada pemahaman tarakib nahwiyyah siswa kelas 11 di Madrasah Aliyah Negeri 4 Cirebon ini menunjukan pengaruh signifikan dan buktinya adalah bahwa hasil penelitian melalui perhitungan paired simple t-test  yaitu dengan hasil sig (2-tailed) 0.000 < 0.005 dan hasil perhitungan cohen’s effect size yaitu 5,55 dengan sampel 31 siswa dengan ini bahwa model pembelajaran Scramble dampaknya dianggap kuat dan tinggi. Maka Ha diterima, HO ditolak.